Effect of cooling rate on the microstructure of rapidly solidified SiGe - Hussain, Naveed; Mullis, Andrew M.; Haque, Nafisul (Materials characterization, 2019)
Si-30 wt% Ge (14.2 at.% Ge) alloy has been subject to rapid solidification by drop-tube processing, with the resulting powders being subject to cooling rates between 1800 and 20,000 K s−1. Microstructure characterisation was conducted via SEM which showed the formation of distinctive Si-rich grains with Ge localised at the grain boundaries in what appeared to be small discrete crystallites. EDX was used to determine the Ge concentration at the grain boundaries wherein contrary to expectation it was found that partitioning increased with increasing cooling rate. EDX performed in the TEM revealed that the Ge-rich regions at the grain boundaries had compound like preferred compositions, with Ge:Si ratios of 3:2 and 7:1 being observed, neither of which would be expected from the phase diagram. However, EBSD and TEM diffraction analysis show that these Ge-rich regions are not distinct compounds, having the same crystal structure and orientation as the Si-rich grain to which they are attached. There is also no evidence for chemical ordering. As such, the origin of these compound like regions of preferred composition remains enigmatic. [Display omitted] •Slow-cooled Si-Ge display low visible partitioning, rapidly solidified microstructures exhibit higher partitioning.•Increased cooling rate results in an increase of partitioning, attributed to back-diffusion.•A previously unknown stoichiometric compound, Ge3Si2, is found.•The potential presence of other stoichiometric compounds is found.